STEAM-Based Learning Implementation Plan: Integrating Science, Technology, Engineering, Art, and Mathematics in Teaching Indonesian Language Education - Imam Safi'i (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
The purpose of this study was to describe the ability of teachers and various factors that support and hinder the ability of teachers in preparing STEAM-based learning implementation plans. The data sources in this study were 30 learning implementation plans that had been prepared by Indonesian language teachers who had participated in teacher professional education training activities at a private university in Jakarta. The method used in this study was content analysis. In addition, data collection was also carried out through structured interviews to explore the opinions of teachers about the supporting and inhibiting factors experienced by teachers in the training of preparing STEAM-based learning plans. The results of the study showed that the average ability of teachers in preparing STEAM-based learning implementation plans was very good, namely (80). This means that they have been able to describe the learning steps using the STEAM approach well. The success factor for teachers in preparing STEAM-based learning implementation plans (LIPs) is influenced by the readiness of the implementing agency, instructors, and the optimal support of certain personnel.